2014
DOI: 10.1128/jb.01584-14
|View full text |Cite
|
Sign up to set email alerts
|

The RimL Transacetylase Provides Resistance to Translation Inhibitor Microcin C

Abstract: MccE is homologous to chromosomally encoded acetyltransferases RimI, RimJ, and RimL, which acetylate, correspondingly, the N termini of ribosomal proteins S18, S5, and L12. Here, we show that E. coli RimL, but not other Rim acetyltransferases, provides a basal level of resistance to McC and various toxic nonhydrolyzable aminoacyl adenylates. RimL acts by acetylating processed McC, which along with ribosomal protein L12 should be considered a natural RimL substrate. When overproduced, RimL also makes cells resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 25 publications
1
34
1
Order By: Relevance
“…coli , thus inactivating it [ 16 ]. RimL possesses the same activity as MccE [ 33 ] and, in addition, converts the ribosomal protein L12 to L7 by acetylating its N-terminal amino group [ 19 ]. PseH, RimL and the acetyltransferase domain of MccE adopt a very similar fold, despite the limited sequence homology (less than 8% global sequence identity and less than 15% identity for pairwise alignments of PseH with MccE and RimM; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…coli , thus inactivating it [ 16 ]. RimL possesses the same activity as MccE [ 33 ] and, in addition, converts the ribosomal protein L12 to L7 by acetylating its N-terminal amino group [ 19 ]. PseH, RimL and the acetyltransferase domain of MccE adopt a very similar fold, despite the limited sequence homology (less than 8% global sequence identity and less than 15% identity for pairwise alignments of PseH with MccE and RimM; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The E. coli acetyltransferases RimI, RimJ, and RimL acetylate the N termini of ribosomal proteins S18, S5, and L12, respectively ( 59 , 60 ). RimL has been shown to acetylate McC lysine residues, resulting in the inactivation of this otherwise toxic peptide-nucleotide antibiotic ( 81 ). Two putative S. meliloti acetyltransferases were identified that show homology to E. coli Rim acetyltransferases ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression and in vivo McC activity tests were done in E. coli B strain. E. coli BW25113 Δ rimI Δ rimL Δ rimJ 11 was used for in vitro Asp-RS inhibition assay. Bacteria were grown on LB medium supplemented with antibiotics as required.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…8,9 Stand-alone cellular homologues of MccE and MccF that are not part of mcc operon also contribute to basal levels of McC resistance. 10,11 …”
Section: Introductionmentioning
confidence: 99%